PENGARUH PEMBERIAN BEBERAPA JENIS PUPUK MAJEMUK PADA BERBAGAI JENIS TANAH TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE-NURSERY - Thuti Thuti; Al Ichsan Amri; Islan Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objective of the research is to seek the influence of the type of compound fertilizer which can be used for different types of soil on palm oil seedling in the pre- nursery. This research was conducted in the experimental field and Laboratory of Production Faculty of Agriculture, University of Riau in Campus Binawidya Km 12.5 Simpang BaruPekanbaru. The research was lasted 4 month from March 2016 until Juny 2016. Completely Rendomized Design (CRD) was used in this research, with two factors. first factor is three types of compound fertilizer and the second factor is planting medium that consists three level. Parameters measured were seedling height, number of leaves, stem diameter, leaf area. Data obtained from the research results were statistically analyzed by analysis of variance followed by a further test of Duncan's New Multiple Range Test (DNMRT) at 5%. Based on factor analysis of variance that soil type sigmificantly affected plant height, number of leaves, core diameter, and leaf area of oil palm seedlings. Whereas factor and the interaction type of compound fertilizer and growing media influence the amount is not significantly affected plant height, number of leaves, core diameter, and leaf area of oil palm seedlings age of four months in Pre-nursery. The key word: the type of compound fertilizer, types of soil, the Oil Palm